2005
DOI: 10.1007/s00442-005-0158-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 influences herbivory-induced defense responses of Arabidopsis thaliana

Abstract: We experimentally demonstrate that elevated CO(2) can modify herbivory-induced plant chemical responses in terms of both total and individual glucosinolate concentrations. Overall, herbivory by larvae of diamondback moths (Plutella xylostella) resulted in no change in glucosinolate levels of the annual plant Arabidopsis thaliana under ambient CO(2) conditions. However, herbivory induced a significant 28-62% increase in glucosinolate contents at elevated CO(2). These inducible chemical responses were both genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 48 publications
1
72
1
Order By: Relevance
“…oleifera) (Himanen et al, 2008). However, in Arabidopsis thaliana CO 2 enrichment did not significantly influence the GS concentration (Bidart-Bouzat et al, 2005). Karowe et al(1997) suggested that responses in GS content to elevated CO 2 concentration appeared to be species-specific, as in the same experiment total GS concentrations in both young and old mustard (Brassica juncea) leaves decreased, whereas GS concentrations in radish (Raphanus sativus L.) and turnip (Brassica rapa subsp.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…oleifera) (Himanen et al, 2008). However, in Arabidopsis thaliana CO 2 enrichment did not significantly influence the GS concentration (Bidart-Bouzat et al, 2005). Karowe et al(1997) suggested that responses in GS content to elevated CO 2 concentration appeared to be species-specific, as in the same experiment total GS concentrations in both young and old mustard (Brassica juncea) leaves decreased, whereas GS concentrations in radish (Raphanus sativus L.) and turnip (Brassica rapa subsp.…”
Section: Discussionmentioning
confidence: 92%
“…rapa) appeared to be unaffected by CO 2 enrichment (724 μl/L). Furthermore, Reddy et al(2004) and Bidart-Bouzat et al(2005) observed that the significant changes in individual GS concentrations were not consistent among cultivars of oilseed rape and Arabidopsis thaliana under elevated CO 2 conditions, supporting the hypothesis that, in general, the response to elevated CO 2 differs among cultivars. Moreover, in Chinese kale bolting stems, the concentrations of aliphatic GS glucoerucin and all individual indolyl GSs were not affected by the elevated CO 2 concentration, indicating that the concentrations of individual GSs within a specific GS group (i.e., aliphatic, aromatic, or indolyl) did not change consistently, which agreed with the conclusion that the response to elevated CO 2 also depends on the individual GS type (Bidart-Bouzat et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…However, there are also biological differences in inducibility among species. In fact, within a species even ecotypes (Bidart-Bouzat et al 2005;Kliebenstein et al 2002) and cultivars (Birch et al 1992(Birch et al , 1996 differ in glucosinolate response to herbivory. Interestingly, plants from a wild population of Brassica oleracea were found to have higher glucosinolate concentrations and higher inducibility after herbivory than plants of a B. oleracea cultivar (Gols et al 2008).…”
Section: Variation By Glucosinolate Typementioning
confidence: 99%
“…Natural genetic variation in the biosynthetic enzymes within Arabidopsis leads to diverse chemical mixtures influencing insect herbivory (Kliebenstein et al, 2001a(Kliebenstein et al, , 2001b(Kliebenstein et al, , 2001c. The accumulation and structural diversity of intact glucosinolates are regulated by plant development and tissue type (Petersen et al, 2002;Reichelt et al, 2002;Brown et al, 2003) and a suite of biotic and abiotic factors (Leach et al, 1999;Agrawal et al, 2002;Kliebenstein et al, 2002;Bidart-Bouzat et al, 2005;Mewis et al, 2006;Kim and Jander, 2007;Reifenrath and Muller, 2007).…”
mentioning
confidence: 99%